A Study on criminal deportation - Barnes, Annmarie (CARICOM Secretariat GeorgetownGY, 2007)
Reviews the legislative, administrative and procedural guidelines that govern the deportation process, with specific focus on the management of serious criminal offenders. Focusses on the development of recommendations for the implementation of appropriate mechanisms to ensure accurate classification, reporting and management of data. Includes policy options for the creation of standardised agreements througout the region, as well as to inform dialogue/negotiation between CARICOM states and the major deporting countries.